A Review on Therapeutic Potential of Justicia adhatoda L. - Jamwal, Mehak; Sharma, Shalini; Puri, Sunil (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Justicia adhatoda L. has been used in the indigenous system of medicine for more than 2000 years. It is distributed throughout tropical and sub-tropical parts of India. It is well-known for its beneficial properties. It is an exclusive herb that helps in improving the bronchial function with bronchodilatory, expectorant and mucolytic properties. The leaves, bark, fruits and flowers are used and considered safe and are recommended for usage and dosing. It possesses the most important bioactive phytochemicals with novel bioactivities that deliver a greater insight into its therapeutic use and also the medicinal value. The therapeutic potential of plant-based medicines to fight diseases is because of the presence of phytoconstituents in different parts of the plant. Medicinal plants possess a great ability to combat various ailments. Various phytoconstituents obtained from Justicia adhatoda L. viz., vasicine, vasicinone, flavonoids, phenols etc., play remarkable role in traditional medicinal system. Further, these compounds display several biological activities for instance, bronchodilatory, antitussive activity, anti-microbial activity, anti-oxidant activity, hepatoprotective activity, cardioprotective activity, anti-allergy activity etc.
Keywords: Bronchodilatory; Justicia adhatoda L.; medicinal; medicine; plants